Efektivitas Media Sosial terhadap Kesadaran Gaya Hidup Sehat Mahasiswa: Tinjauan Hukum Kesehatan - Reny Suryanti; Ade Sissca Villia; Ade Zayu Cempaka Sari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Advances in information and communication technology today have a significant impact on life in various aspects, including the dissemination of health information. Students of productive age are vulnerable to lifestyle changes due to activity patterns, academic demands, and access to fast food (WHO.2023). Health campaigns run through social networks, including Instagram and TikTok, have been shown to be effective in influencing behavior change (Aisyah et al., 2023). This research method is descriptive qualitative. The population and samples used were Bengkulu Poltekkes students who actively use social media. The results showed that the use of social media platforms such as Tik Tok, Youtube, Facebook, Instagram and Twitter was effective in increasing awareness of healthy lifestyles in students. As well as encouraging changes in student behavior towards a healthier lifestyle. the relationship between health legal regulations and the use of social media as a means of healthy lifestyle education is mutually supportive and mutually needy.